2018
DOI: 10.2319/101317-691.1
|View full text |Cite
|
Sign up to set email alerts
|

Dentoalveolar effects produced by different appliances on early treatment of anterior open bite: A randomized clinical trial

Abstract: All of the tested devices promoted dental changes, especially in the anterior region, and contributed to AOB reduction during the study period. However, fixed palatal crib demonstrated greater impact on the positioning of the incisors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
42
1
11

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(66 citation statements)
references
References 23 publications
12
42
1
11
Order By: Relevance
“…Also, in the current study, a significant increase of 5.57°in the interincisal angle was observed, due to the retroclination of the anterior teeth. Similarly, previous studies observed an increase in the interincisal angle ranging from 9.66°( palatal crib and chincup) [16], 3.34°(BS), 9.65°(FPC), 7.01°(RPC), and 4.25°(CC) [8].…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Also, in the current study, a significant increase of 5.57°in the interincisal angle was observed, due to the retroclination of the anterior teeth. Similarly, previous studies observed an increase in the interincisal angle ranging from 9.66°( palatal crib and chincup) [16], 3.34°(BS), 9.65°(FPC), 7.01°(RPC), and 4.25°(CC) [8].…”
Section: Discussionsupporting
confidence: 81%
“…Extrusion arch mechanics produced a mean maxillary incisor extrusion of 1.94 mm during a mean treatment period of 7.79 months. Previous studies observed similar results with other types of appliances over a 12-month period [8,9,14,16,17]. The removable palatal crib (RPC) resulted in incisor extrusion ranging from 1.64 mm [8], 2.47 mm [9], and 2.98 mm [17], while the use of bonded spurs (BS) promoted changes of 1.50 mm [8], 2.35 mm [9], 3.16 mm [16], and 2.33 mm [17] when associated with a chincup (CC) [16].…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…In children and adolescents, anterior open bites with tongue thrust can be treated by fixed or removable appliances, with or without lingual spurs and cribs. [45][46][47] However, anterior open bites in adult patients are considered skeletal, since the positioning of the anterior teeth implies in permanently deformed dentoalveolar bases and, most of the time, malocclusion is treated with fixed orthodontic appliances and intermaxillary elastics. 48 Indeed, an orthodontic-surgical approach, with mandibular advancement and counterclockwise rotation of the occlusal plane, can be an alternative therapeutic plan for these cases 49 But orthognathic surgeries involve extra costs and risks, and provide no full guarantee of long-term stability.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the use of the fixed palatine grille for the treatment of anterior open bite, the present report is in agreement with previous studies, which opted for the same treatment, being successful at the end of the therapy. 29,30…”
Section: Discussionmentioning
confidence: 99%